COMMUNICATION STRATEGY USED BY PT GRAB INDONESIA IN MAINTAINING DRIVER-PARTNER LOYALTY - Ketut Alit Pratiwi; Andre Rahmanto; Sudarmo (Unmas Press, 2021)
Employee loyalty is one of the most important things that must be maintained by a company. Grab is a transportation company that focuses on maintaining the loyalty of its driver-partners. Therefore, the Grab company can survive until now. The Grab company then made an innovation, namely Grab Benefit to provide benefits to drivers in the hope of increasing driver loyalty. This study focused on analyzing the management of communication strategy used by PT Grab Indonesia in providing benefits to the drivers to increase the loyalty of their driver-partners. This research made use of the qualitative research method and the data collection was conducted through interviews. The results of this study showed that Grab Benefit is currently able to provide benefits to their drivers where all driver needs are provided from basic needs to entertainment for drivers. In addition, to grab benefits, Grab also holds Night Appreciation Partner which is run every year to give rewards to driver-partners who excel. It is not only for drivers, but their family members also get the benefits provided by Grab, one of which is scholarships for driver-partner children. Grab also provides a place for driver-partners to express their complaints, a discussion activity between driver-partners and representatives from Grab. Furthermore, this study implies that communication strategy is important to be developed to maintain sustainable drivers’ loyalty towards Grab company.